Breeding of F, hybrids in muskmelon: Accomplishment and Prospects (Indian Journal of Arid Horticulture, 2025)
Heterosis breeding has been extensively explored and utilized in muskmelon. Being cross pollinated crop and its ability to produce plenty of seeds per fruit facilitates heterosis breeding and make it economically viable. Presence of different pollination mechanisms like monoecy, gynoecy and genetic male sterility could be effectively explored for economic production of F, hybrids. A large number of varieties have been developed through continuous inbreeding and selection without losing vigour, which is unexpected in cross pollinated crops. Now there is need to give the attention to develop high quality (TSS) and disease resistant hybrids utilizing economic tools.
Keywords: pollination; Heterosis; heterosis; viable; monoecy